LEARNING TO CLASSIFY: ONLINE VERSUS PRINTED DEWEY - Hider, Philip (Malaysian Journal of Library and Information Science, 2004)
Two versions of the Dewey Decimal Classification (DDC) scheme were offered as options to distance education students at Charles Sturt University (CSU) as the basis for their study and eventual application of it; the traditional printed version and the new online version called WebDewey. Students were provided with the same supporting materials. A study was carried out to examine whether the students’ use of a particular version of DDC affected their learning. Despite the author’s concerns about teaching elementary classification using the online version, no significant difference in performance between students who used WebDewey and students who used the printed volumes was found, although on the average the sample using the latter did perform a little better in the assessment. Neither were significant differences in aspects of DDC classification found. Nevertheless, the conclusions may not hold true for other online products, nor for other educational contexts, and educators must take care to consider each product’s effectiveness as a teaching medium, irrespective of the current trend in favour of online materials. In any case, a revision of supporting materials when an online product replaces a printed one may well be worthwhile